(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
The report presents the creative path developed during the work process of the “Light Experience Project and the Retelling of Haunting Stories in the City of Belém-2021”, which addressed creative scenic lighting through experiences with lighting in community spaces on the outskirts of the city.